Handover algorithm using fast DAD mechanism for hierarchical mobile IPv6 - CHEN Wei-xin; HAN Guo-dong; LIU Hong-bo; CAI Hui (Tongxin xuebao)
To solve the problem that the duplicate address detection （DAD） in hierarchical mobile IPv6 （HMIPv6） links too time consuming, a handover algorithm based on fast DAD mechanism for HMIPv6 was proposed. By introducing the IP address allocation management （IAAM） module to establish the DAD-lookup and initiative address-generation mechanism, the proposed algorithm can greatly speed up the DAD course and be implemented easily. Simulation results showed the HMIPv6 optimized by the algorithm （F-DAD-HMIPv6） could reduce intra-domain handover delay and in- ter-domain handover delay to 202ms, 339ms respectively and was superior to MIPv6 and HMIPv6.